Dinamika Kinerja Aparatur dalam Mewujudkan Akuntabilitas Pelayanan Kelurahan - Mustari, Nuryanti; Anto; Salimang (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
Performance accountability of public agencies, including the Rampoang Sub-district Office of Palopo City, is crucial to ensure the government's responsibility to the community. However, it is often not fully realized, leading to problems such as slow administrative services and lack of integrity among staff. The researcher's analysis has revealed that there has been no previous study linking the accountability of the staff with the provision of services in Rampoang Village, Palopo City. This study aims to address this gap and examine the accountability of staff performance in the implementation of services in Rampoang Village, Palopo City. This research utilizes a quantitative descriptive method, gathering data through observation, interviews, and documentation. The results indicate that the expected level of accountability in the Rampoang Village office has not been met due to a shortage of human resources in the staff. This has resulted in slow delivery service to the community, with minimal accountability among the staff. Public complaints regarding services, particularly relating to process accountability and honesty, are still widespread in the Rampoang Village office. As a result, the researchers propose several recommendations. One of these is the need to increase the number of staff members, as this can have an impact on the provision of services in the Rampoang Village office. Data from the village office indicates that while there is satisfaction with the speed of service and the behavior of the staff, concerns remain regarding time efficiency, service quality, and transparency in costs. This highlights the necessity for improvement in these areas.